(untitled) (Journal of Computational Mathematics, 1984)
Let l and u be upper and lower semicontinuous extended functions on [a,b], respectively, with l≤u. Let H be an n-dimensional Haar subspace and K={pH:l≤ p≤ u}. This paper gives complete characterizations of K satisfying card K=0 or 1 or ∞ under certain assumptions, where card K denotes the cardinality of K.